Cardiolipin alterations and mitochondrial dysfunction in heart ischemia/reperfusion injury. (October 2015) - Paradies, Giuseppe; Paradies, Valeria; Ruggiero, Francesca M; Petrosillo, Giuseppe
Mitochondrial dysfunction is centrally involved in heart ischemia/reperfusion (I/R) injury. Increased reactive oxygen species production, impaired respiratory chain complexes activity and opening of the mitochondrial permeability transition pore have been suggested as possible factors responsible for mitochondrial dysfunction in heart I/R injury. Cardiolipin (CL), a phospholipid of the inner mitochondrial membrane, plays an important role in mitochondrial bioenergetics. CL alterations have been shown to play a causative role in mitochondrial dysfunction in a variety of pathological conditions, as well as in cell death. The role of CL alterations in mitochondrial dysfunction in heart I/R injury is here reviewed. Several cardioprotective strategies to prevent myocardial injury during I/R targeting mitochondrial CL are also examined.